2018
DOI: 10.1080/19440049.2017.1411611
|View full text |Cite
|
Sign up to set email alerts
|

Potential silver nanoparticles migration from commercially available polymeric baby products into food simulants

Abstract: In recent years, silver nanoparticles (AgNPs) have been extensively employed in food packaging systems as a potential antibacterial agent. Although proven to be highly effective, the increased number of AgNP-containing products raises concerns among consumers regarding the migration of AgNPs from the packaging material into foods, which may exert toxic effects. To address this, five baby products were chosen (baby bottle A, baby bottle B, pacifier A, pacifier B and breastmilk storage bag) to investigate AgNPs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…Thus, the presence of AgNPs in dietary supplements, water contamination, or food fish and other aquatic organisms provides the potential sources of oral exposure [23]. Recent studies have also demonstrated that AgNPs incorporated in food packaging can migrate from packaging into food under several usage conditions [95,96]. Inhalation exposure during manufacturing also ultimately leads to oral exposure, since particles cleared via the mucociliary escalator are swallowed and cleared through the GIT.…”
Section: Oral Exposurementioning
confidence: 99%
“…Thus, the presence of AgNPs in dietary supplements, water contamination, or food fish and other aquatic organisms provides the potential sources of oral exposure [23]. Recent studies have also demonstrated that AgNPs incorporated in food packaging can migrate from packaging into food under several usage conditions [95,96]. Inhalation exposure during manufacturing also ultimately leads to oral exposure, since particles cleared via the mucociliary escalator are swallowed and cleared through the GIT.…”
Section: Oral Exposurementioning
confidence: 99%
“…If PNCs find use as food contact materials, they could potentially be a source of human dietary exposure to engineered nanomaterials (ENMs). Consequently, studies have explored whether nanofillers can transfer out of PNCs into foods and other environments under intended use conditions. , This body of work has mostly focused on silver nanoparticles (AgNPs), but nanoclay, , metal oxide, , carbonaceous, or other nanofillers have also been investigated. These studies have established that nanofiller mass (e.g., Ag) is usually released from PNCs during long-term storage, and factors like food pH, embedded particle characteristics (size, composition), and polymer properties impact this process.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the antimicrobial potential of silver nanoparticles (AgNPs), they are amongst the most frequently used nanoparticles (NPs) in food associated products (e.g. packaging and kitchen utensils) (Choi et al 2018;Lichtenstein et al 2015). Therefore, oral ingestion is considered as a main exposure route for humans to AgNPs.…”
Section: Introductionmentioning
confidence: 99%